Developing and analyzing items of a physics conceptual understanding test on wave topics for high school students using the Rasch Model - Rasyid, Fauziah; Istiyono, Edi; Gunawan, Cahya Widya; Kijambu, John Baptist (REID (Research and Evaluation in Education), 2025)
This study aims to develop, validate, and analyze test items for assessing the understanding of mechanical wave concepts among high school students. The test development process followed the Mardapi instrument development model, which includes: (1) constructing test specifications, (2) writing test items, (3) reviewing test items, (4) piloting the test, and (5) analyzing the items. The developed instrument consists of 12 multiple-choice items, covering three aspects of conceptual understanding: translation, interpretation, and interpolation. Content validity was assessed by three validators, and the results were analyzed using the Aiken V method. The instrument was then administered to 257 high school students in South Sulawesi Province. The results were analyzed using Item Response Theory (IRT) with the Rasch model through the Quest program. Item analysis included item fit estimation, reliability, and item difficulty. The content validity test results indicate that the instrument is valid. All items fit the Rasch model, with a reliability coefficient of 0.95, categorized as high reliability. Item difficulty analysis revealed that 8.3% of items were categorized as easy, 8.3% as difficult, and 83.3% as moderate. Overall, the results indicate that the test instrument is of good quality and can be used to assess high school students’ understanding of mechanical wave concepts.